Effect of four different starting stances on sprint time in collegiate volleyball players - Johnson, T. M.; Brown, L. E.; Coburn, J. W.; Judelson, D. A.; Khamoui, A. V.; Tran, T. T.; Uribe, B. P. (The Journal of Strength and Conditioning Research, 2010)
Starting stance plays an important role in influencing short-distance sprint speed and, therefore, the ability to reach a ball during sport play. The purpose of this study was to evaluate 4 different starting stances on sprint time. Twenty-six male and female collegiate volleyball players volunteered to participate in 1 testing session. Each subject performed 3 15-ft sprint trials at each of 4 different starting stances (P-parallel, FS-false step, S-staggered, and SFS-staggered false step) in random order. Analysis of variance revealed that there was no significant interaction of sex by stance, but there were main effects for sex (men were faster than women) and stance. The FS (1.18 ± 0.10 seconds), S (1.16 ± 0.07 seconds), and SFS (1.14± 0.06 seconds) stances were faster than the P (1.25 ± 0.09 seconds) stance, and the SFS stance was faster than the FS stance. This indicates that starting with a staggered stance (regardless of stepping back) produced the greatest sprinting velocity over the initial 15 feet. Although taking a staggered stance seems counterproductive, the resultant stretch-shortening cycle action and forward body lean likely increase force production of the push-off phase and place the total body center of mass ahead of the contacting foot, thereby, decreasing sprint time.